NORTH STATE PROJECTS A VERY ACTIVE LEGISLATIVE SESSION IN MINNESOTA THIS YEAR (Tufts Archival Research Center, 2007)
Letter from David M. Horazdovsky of North State Advisors, to Michael Brozek of the Tobacco Institute regarding the three issues in which he foresees much legislative activity in the state of Minnesota. Includes: tax increases, sampling and the Clean Indoor Air Act.